The Effectiveness of Village Funds in Alleviating Rural Poverty: A Case Study of Belitung Regency - Asep Hariyanto; Bambang Juanda; Ernan Rustiadi; Sri Mulatsih (MIMBAR : Jurnal Sosial dan Pembangunan, 2023)
Poverty is always synonymous with disadvantaged people in rural and urban areas. According to the OECD (2016) three billion people in developing countries, including Indonesia, live in rural areas, and the majority are poor. The government has made various efforts in Indonesia to alleviate poverty, including through the concept of "building from the periphery" by allocating considerable funds to strengthen rural development. This study aims to measure the effectiveness of village funds in alleviating poverty in rural areas (case study: Belitung Regency) using the Moran's Index Analysis and Geographically Weighted Regression (GWR) analysis methods. Based on the results of Moran's Index analysis on poverty levels in 42 villages in Belitung Regency, it can be seen that the distribution pattern of poverty in each village is random or unpredictable. At the same time, the effect on poverty shows that village funds in the field of government administration have not influenced poverty alleviation. Meanwhile, the fields of development implementation, community development, community empowerment, disaster management, and emergencies, and urgency affect poverty alleviation as indicated by a "negative" regression coefficient.